Strategic design under uncertain evaluations: structural analysis of design‐build auctions. - Takahashi, Hidenori (RAND Journal of Economics (Wiley-Blackwell))
Abstract: I investigate firms' competition over price and product design under uncertain design evaluations in the context of Design‐Build (DB) auctions. Reviewers' design evaluations contain uncertainty from a bidder's perspective, leading luck to dampen differences in the firms' chances of winning. I model bidders' behavior and show semiparametric identification of the model primitives. Uncertain design evaluations increase the expected price of design quality and exacerbate an auctioneer's uncertainty in auction outcomes. These effects are mostly due to changes in bidding strategies. Bid ranking swaps due to uncertain evaluations account for a small share of these effects.